Efeito anti-adiposidade da Mucuna Pruriens L.: um enfoque sobre parâmetros neurocomportamentais, metabólicos e de saúde intestinal de ratos com obesidade - Tavares, Renata Leite (2020)
Obesity is a growing public health problem. Its treatment includes behavioral changes, physical exercise, dietary intervention and allopathic or herbal medicines. Mucuna pruriens L. (MP) is a medicinal plant that has stood out for its phytochemical composition, rich in antioxidant and anti-inflammatory substances, which can be adjuvant in the treatment of obesity. Thus, this study aimed to evaluate the effect of MP treatment on neurobehavioral, metabolic and intestinal health parameters of healthy and obese rats. The proximate composition was determined; oligosaccharides and profile of MP phenolic compounds. Thirty-two Wistar rats with ± 40 days of age were used, initially randomized in the healthy (HG, n = 16) and obese (OG, n = 16) groups. HG consumed control chow diet and OG consumed cafeteria diet for eight weeks. Then, they were subdivided into the groups: healthy (HG, n = 8); healthy treated with MP (HGMP, n = 8); obese (OG, n = 8); obese treated with MP (OGMP, n = 8), the consumption of the respective diets remaining for another eight weeks, in addition to the gavage with extract of MP seeds to the supplemented groups (750 mg / kg weight). Food consumption and body weight were monitored. In the last week, the animals 'anxiety and depression behavior was evaluated, glucose tolerance and insulin resistance tests were performed and the animals' faeces were collected for bacterial count and quantification of organic acids. On the day of euthanasia, murinometric parameters were measured and adipose tissue, liver and intestine were removed for histological analysis and the brain was also used for immunohistochemical analysis with interleukin-6. Inflammatory markers, hormones and lipid profile were evaluated in the serum and with these results, the metabolic load index and homeostasis assessment model (HOMA index) were calculated. With carcasses, body composition was evaluated. The MP presented a composition rich in proteins (7.11%), levodopa (14.08%) 1-kestose oligosaccharide (20.70 mg / 100g) and phenolic compounds such as catechins (57.83 mg), chlorogenic acid (49, 32 mg), trans- resveratrol (21.41 mg) and kaempferol 3-glycoside (57.83 mg). Behavioral tests indicated anxiolytic and antidepressant effects of MP in obese rats. The treatment was effective in reducing food consumption (17%), body weight (14%), percentage of fat mass (44%) and body mass index (12%) in obese animals. Regarding to the lipid profile, there was a reduction in triglycerides (68%), an increase in HDL cholesterol (45%) and a reduction in the metabolic load index (24%) in OGMP versus OG. The hormones insulin and leptin, the HOMA index, C-reactive protein and alpha-1-acid glycoprotein had reduced levels in OGMP when compared to OG. MP treatment reversed brain inflammation, as well as liver and adipose tissue changes in OGMP animals. MP treatment increased the count of latic acid bacteria and the amount of organic acids in faeces. Thus, the results on the anti-adiposity effect of MP are promising, making it a possible adjuvant in the treatment of obesity.